Specific Deubiquitinating Enzymes Promote Host Restriction Factors Against HIV/SIV Viruses - Gao, Wenying; Rui, Yajuan; Li, Guangquan; Zhai, Chenyang; Su, Jiaming; Liu, Han; Zheng, Wenwen; Zheng, Baisong; Zhang, Wenyan; Yang, Yongjun; Hua, Shucheng; Yu, Xiaofang (Frontiers in Immunology, 2021)
Hijacking host ubiquitin pathways is essential for the replication of diverse viruses. However, the role of deubiquitinating enzymes in the interplay between viruses and the host is poorly characterized. Here we demonstrate that specific deubiquitinating enzymes are potent inhibitors of viral proteins from HIV/SIV viruses that are involved in viral evasion of host restriction factors and viral replication. In particular, we discovered that T cell-functioning ubiquitin-specific protease 8 (USP8) is a potent and specific inhibitor of HIV-1 Vif-mediated APOBEC3G (A3G) degradation. Ectopic expression of USP8 inhibited Vif-induced A3G degradation and suppressed wild-type HIV-1 infectivity even in the pres-ence of Vif. In addition, specific deubiquitinating enzymes repressed Vpr, Vpu and Vpx-triggered host restriction factors degradation. Our study has revealed a previously unrecognized interplay between the host’s deubiquitinating enzymes and viral replication. Enhancing the anti-viral activity of deubiqui-tinating enzymes therefore represents an attractive strategy against HIV/SIV viruses.